The Differences of Learning Outcomes (Concept Understanding and Concept Application) Students Through Problem Based Learning and Direct Instruction Learning Strategies - Juliati Koesrini; Rachma Putri Kasimbara (Universitas Pahlawan Tuanku Tambusai, 2022)
At the beginning of early life there is a learning process called problem based learning (PBL). PBL learning strategies are very effective in nursing schools. The purpose of this study was to determine the differences in learning outcomes (concept understanding and application) between student teams using PBL and student teams using DI. This study uses pre-experimental quantitative research techniques. Second semester DIII nursing students are the population of this study, totaling 194 students (there are 3 parallel classes, namely class A, B, and C with 65 students in class A, 62 in class B, and 67 in class C), while the sample In this study, there were 67 students in the second semester of the Diploma III Nursing study program, the sampling technique used was cluster random sampling. All data were analyzed using SPSS 20 software for windows with a significant level of 5% (α = 0.05). The results showed (1) there were significant differences in understanding basic nursing concepts (2) there were significant differences in the application of basic nursing concepts in DI. So that in understanding the concept and application of the PBL concept it is superior to DI.